(untitled) - Bailey, Philip S. (New Jersey, 2000)
This application-based book presents essential, core concepts of basic organic chemistry in an engaging, easy-to-read format. It is ideal for the individual seeking a hands-on approach to understanding structure, nomenclature, physical properties, uses and applications, and chemical reactions of organic compounds. Unique engaging techniques get the reader involved in the learning process, such as a "Getting Involved" feature at the end of each section and several dozen mini-essays which connect theory to real life issues. Ideal for medical health professionals and anyone involved in consumer health issues.
Keywords: Chemistry, organic